Quantum Chemistry Study on Structure-Activity Relationship of Pyrimidinyl Thiourea Derivative - Bi, Hui-Min; Xie, Peng-Tao; Chai, Xing-Quan; Liu, Yan; You, Fu-Ying; Hu, Jun-Ping; Zhang, Jing (Asian Journal of Chemistry, 2013)
In order to investigate the relationship between the structure and the activity of pyrimidinyl thiourea derivative, the geometry optimization and single point energy of all compounds were calculated by HF methods at 6-31G* basis sets level, the information of electron density, energy levels, main composition and proportion of the frontier orbitals were obtained. It is found that the antifungicidal activities of these kinds of compounds have a relationship with the energy of frontier molecules orbital (HOMO and LUMO).